A study on the effects of various combustion parameters on the mineral composition of Tunçbilek fly ash. (1st September 2020) - Akın, Süleyman Şener; Magalhães, Duarte; Kazanç, Feyza
Abstract: This study investigated the mineral composition and morphology of ash obtained from laboratory equipment and power plant fly ash from a Turkish lignite. In accordance with this purpose, combustion experiments were conducted for different heating rates in a temperature range of 800–1000 °C using different laboratory scale equipment: drop tube furnace (DTF) ( 10 5 °C/s), wire mesh reactor (WMR) ( 10 3 °C/s) and muffle furnace (MF) ( 10 °C/min). The resulting ashes were compared with the ones obtained from power plant. The main phases present in all ashes were quartz, mullite, and hematite. Temperature increase resulted in an increase of mullite and hematite for both muffle furnace (11–14%) and drop tube furnace (6–8%) ashes. The heating rate and residence time had a definite effect on the kaolinite phase. At high heating rates (10 5 °C/s), kaolinite was still present at 1000 °C, whereas at lower heating rates (1 °C/s and 10 3 °C/s), it was not. A decrease in ash crystallinity from 43 to 33% was observed with an increase in heating rate from 1 to 10 5 °C/s. The temperature and the residence time were decisive factors on ash crystallinity. Power plant fly ash (high temperature, short residence time) and muffle furnace ash (low temperature, long residence time) presented the highest crystallinity (48 and 43%, respectively) among all combustion equipment. In general, MF and WMR ashes showed similar morphology; on the other hand, DTF ashes resembled the ones from PP.